মিঞা অসমিয়া এনআরসি আসামে জাতিবাদী বিদ্বেষ ও বাংলাদেশ (ঢাকা : প্রথমা প্রকাশন, 2020)
Articles on illegal immigrant and ethnicity issue in Assam, and introduction of National Register of Citizens (NRC); includes articles on its effect on Bangladesh.
Akbar Ali Khan Collection
In Bengali.
Keywords: Illegal immigration -- India -- Asam